2022
DOI: 10.21203/rs.3.rs-1103049/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Computer Vision Syndrome and Patterns of Electronic Devices Usage before and during COVID-19 Pandemic among Medical Students in Riyadh, Saudi Arabia

Abstract: Purpose: To estimate the prevalence of CVS (computer vision syndrome) among university medical students in Riyadh, Saudi Arabia after establishing remote learning during COVID-19 pandemic and to compare patterns and settings of electronic devices used by students before and during this pandemic. Methods: This is an observational descriptive cross-sectional study. 1st to 5th year medical students actively enrolled at the governmental colleges of medicine in Riyadh were asked to fill an electronic online questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similar findings were found in a study on 300 medical students in Riyadh, Saudi Arabia, which showed a high percentage of subjects experiencing the symptoms of CVS. In that study, 38% of the subjects experienced more severe symptoms, and 48% experienced symptoms with a higher frequency during the COVID-19 pandemic than before 23 . Therefore, preventive measures should address this issue and prevent CVS from persisting or worsening.…”
Section: Resultsmentioning
confidence: 78%
“…Similar findings were found in a study on 300 medical students in Riyadh, Saudi Arabia, which showed a high percentage of subjects experiencing the symptoms of CVS. In that study, 38% of the subjects experienced more severe symptoms, and 48% experienced symptoms with a higher frequency during the COVID-19 pandemic than before 23 . Therefore, preventive measures should address this issue and prevent CVS from persisting or worsening.…”
Section: Resultsmentioning
confidence: 78%
“…They showed that risk factors for three or more CVS symptoms were common among students who used electronic devices for longer periods of time (6.8 hours ±2.8) during COVID-19. The longer the duration of use of the aforementioned devices, the more severe and frequent the symptoms [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms of CVS are eye fatigue, headache, blurred vision, dry eyes and neck and shoulder pain. In addition, improper lighting, inadequate viewing distance and poor sitting posture can aggravate and worsen these symptoms [3].…”
Section: Introductionmentioning
confidence: 99%